"The art of scientific investigation" and "The logic of scientific inference" - SN Arseculeratne (Anuradhapura Clinical Society, 2013)
The contemporary modes of "medical Education" in Sri Lankan faculties of medicine are briefly reviewed. What are missing are discussions on rational practice of scientific research including the use of proper controls, an understanding of the role of logical inference from research results, and a knowledge of the basic philosophy of modern science; this lack results in a state of scientific illiteracy that leads to misconceptions in the interpretation of research findings. A further desideratum is an awareness of the preceding, valid, published literature. Illustrations from the research literature are provided in illustration of the consequences of these deficiencies. None of the Sri Lankan universities, except the Open University as far as the author is aware, includes discussions on the Philosophy of Modern Science in their curricula.